Congregate Meal Program—How Can We Make It More Appealing? (P16-014-19). (13th June 2019) - Schultz, Savannah; Francis, Sarah; Russell, Carlene; Getty, Tim
Abstract: Objectives: Congregate meal program (CMP) participation has been steadily declining despite a growing older adult population. The CMP is an important community nutrition program for older adults. Understanding the needs and preferences for the CMP by older adults is imperative if CMP participation is to increase. The purpose of this study was to identify the motivators and barriers for CMP attendance, menu preferences, desired environmental attributes, and educational programming ideas. Methods: Participants were recruited via in-person presentations and personal invitations in two Midwest urban counties. Four focus groups were held. Three groups were with CMP participants ( n  = 21) and one with non-CMP participants ( n  = 11). All ( n  = 33) completed a sociodemographic questionnaire. Focus group transcriptions were analyzed for themes using standard focus group protocol. Sociodemographic data were analyzed via SPSS using descriptive statistics. Results: All were White. The majority were educated (75.8% some college or higher), female (72.2%), and were food secure (93.8%). Over half (53.1%) aged 71 to 80 years old. Participants stated successful aging required support systems, health care access, financial security, community activities for older adults, and transportation. CMP participation motivators were socialization, affordability, access to a healthy meal and location. Participation barriers for non-CMP participants were being unaware of a CMP near them, limited transportation and not feeling that they needed to participate. Preferred marketing strategies included word of mouth and print-based advertisement. Participants stated that ideally, the CMP would be held in a facility with a welcoming ambience, offer menu choice, and provide a variety of extracurricular activities. Conclusions: These findings provide insight as to how the CMP may be modified to be more appealing to older adults. We suggest CMP promotion highlight the value of a healthy meal and the opportunities for socialization. Funding Sources: Administration for Community Living/Administration on Aging: Innovations in Nutrition Program and Services Grant 2017–2019. https://bit.ly/2RR17VC .